Exploring the indigenous knowledge systems to respond to coronavirus infection 2019 in Cameroon - Tsouh Fokou, Patrick Valere; Youmsi Fokouo, Roger Ducos (Ethnobotany Research and Applications, 2020)
Background: Control of coronavirus infection 2019 outbreaks lack specific vaccine or drugs, highlighting the need for appropriate interventions. Indigenous knowledge has been a source of medicinal agents for thousands of years and could help to circumvent this threat. We sought to know the current indigenous knowledge used to protect against covid-19 by people living in Yaounde and Douala, Cameroon. Methods: This survey was conducted with two-hundred and seventy-seven participants. A semi-structured questionnaire aiming at understanding of the practice and common interventions use by people to prevent covid-19 infection. Interviews were conducted by telephone and face to face interviews. Results: A total of thirty-nine recipes consisting in thirty-eight distinct ingredients were recorded. The recipe ingredients comprising twenty-nine medicinal plants and nine other alternatives were used for covid-19 prevention in the city of Yaounde and Douala, Cameroon. The twenty-nine medicinal plant species corresponded to twenty-eight genera, arranged in twenty-one plant families. The most cited plants in recipes were Citrus aurantiifolia Christm., Zingiber officinale Roscoe, and Allium sativum L.. The most cited formulation besides the basic protective measures consisting in recipe 6 [Allium sativum L., Citrus aurantiifolia (Christm.) Swingle. and Zingiber officinale Roscoe (RFC=Relative frequency of citation 15.16%)]. Leaves were the most commonly utilized plant part with a frequency of 45%. From the thirty-nine recipes recorded, majority were decoction (69.23%; 27/39) and were administered orally. Conclusions: Results show common knowledge devoid of scientific proof for most hints. Thus, we emphasize the richness of popular knowledge, the need further experimental confirmation of their potency for its integration as complementary therapy. Keywords: Complementary medicine, Covid-19, Medicinal plants, Ethnobotanical survey, Knowledge, Self-reported practice.